Mutations changing tropomodulin affinity for tropomyosin alter neurite formation and extension - Natalia Moroz; Laurent Guillaud; Brinda Desai; Alla S. Kostyukova (PeerJ, 2013)
Assembly of the actin cytoskeleton is an important part of formation of neurites in developing neurons. Tropomodulin, a tropomyosin-dependent capping protein for the pointed end of the actin filament, is one of the key players in this process. Tropomodulin binds tropomyosin in two binding sites. Tmod1 and Tmod2, tropomodulin isoforms found in neurons, were overexpressed in PC12 cells, a model system for neuronal differentiation. Tmod1 did not affect neuronal differentiation; while cells expressing Tmod2 showed a significant reduction in the number and the length of neurites. Both tropomodulins bind short α-, γ- and δ-tropomyosin isoforms. Mutations in one of the tropomyosin-binding sites of Tmod1, which increased its affinity to short γ- and δ-tropomyosin isoforms, caused a decrease in binding short α-tropomyosin isoforms along with a 2-fold decrease in the length of neurites. Our data demonstrate that Tmod1 is involved in neuronal differentiation for proper neurite formation and outgrowth, and that Tmod2 inhibits these processes. The mutations in the tropomyosin-binding site of Tmod1 impair neurite outgrowth, suggesting that the integrity of this binding site is critical for the proper function of Tmod1 during neuronal differentiation.